Gestão do valor de marca nas ações de ponto-de-venda - Souza, Lucy de Lira (2007)
The purpose of this study was to study the role and the importance of the point of sale (POS) in the process of brands management. By means of the analysis of models of brand management, the main sources that determine value to the brand have been identified and, from this analysis, it was developed an instrument for the evaluation of POS actions. Thus, in order to reach the goal proposed, a qualitative research was developed, where the POS actions that won the Popai Brasil 2006 Award were assessed, according to the evaluation instrument. The application of the instrument showed that some of the sources that generate equity, such as the brand knowledge and the associations to the brand, can be easily worked on in the supermarket stores. However, the quality noticed and the loyalty to the brand are more complex aspects to be operationalized in the POS actions. The theoretical study and the empirical verification showed that the POS has an impact function in the work of brands management. In spite of the commercial and short term aspect, the POS actions must be seen as a strategic element in the marketing composition. Therefore, given their relevance, it is important that the managers determine if the work of the brands in the POS is in accordance with the positioning and the image that the company intends to convey to its consumers